Impact of AlN Seed Layer on Microstructure and Piezoelectric Properties of YxAl1−xN (x = 15%) Thin Films - Shardul Pandit; Michael Schneider; Claudio Berger; Sabine Schwarz; Ulrich Schmid (Advanced Electronic Materials, 2023)
Abstract Alloying transition metals into aluminum nitride (AlN) has surged over the past decade to increase the piezoelectric performance of AlN for microelectromechanical systems (MEMS) applications. So far, the highest piezoelectric coefficients have been achieved by alloying scandium into AlN. But, most recently published studies have theoretically predicted by ab‐initio calculations that yttrium can also be a promising and less expensive alternative to scandium. This paper focuses on the impact of an AlN seed layer on the growth and piezoelectric properties of sputter‐deposited, polycrystalline Y0.15Al0.85N thin films on a silicon substrate. For the first time, the increase in piezoelectric performance of YxAl1−xN (x = 15%) thin films with a d33 of ≈7.85 pC N−1 due to this seed layer approach is presented, thus reaching in good agreement theoretical predictions. Furthermore, for the first time, the crystalline stability of Y0.15Al0.85N layers in a pure oxygen environment up to 1200 °C is reported, demonstrating a high oxygen resistance up to 800 °C even in this harsh environment. Detailed thin film analysis is done with various techniques such as X‐ray diffraction, atomic force microscopy, nano‐indentation, and high‐resolution transmission electron microscopy and correlated with piezoelectric coefficient measurements.